2013
DOI: 10.1371/journal.pone.0063556
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of Nutritional Ant–Plant Interaction: Ant Partners of Carnivorous Pitcher Plants Prevent Nutrient Export by Dipteran Pitcher Infauna

Abstract: Many plants combat herbivore and pathogen attack indirectly by attracting predators of their herbivores. Here we describe a novel type of insect–plant interaction where a carnivorous plant uses such an indirect defence to prevent nutrient loss to kleptoparasites. The ant Camponotus schmitzi is an obligate inhabitant of the carnivorous pitcher plant Nepenthes bicalcarata in Borneo. It has recently been suggested that this ant–plant interaction is a nutritional mutualism, but the detailed mechanisms and the orig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 55 publications
0
26
0
1
Order By: Relevance
“…These may be bigger or smaller in plants with ants, depending on the energy-balance between plant and ant mutualists (Frederickson & Gordon, 2009). Such between-individual variation has also been recorded for mutualisms insects and carnivorous plants (Scharmann et al, 2013). As a result, in a system with defensive ant mutualists, the simple predictions of optimal foraging (i.e.…”
Section: Species Studiedmentioning
confidence: 70%
“…These may be bigger or smaller in plants with ants, depending on the energy-balance between plant and ant mutualists (Frederickson & Gordon, 2009). Such between-individual variation has also been recorded for mutualisms insects and carnivorous plants (Scharmann et al, 2013). As a result, in a system with defensive ant mutualists, the simple predictions of optimal foraging (i.e.…”
Section: Species Studiedmentioning
confidence: 70%
“…Analogies can be drawn with sea anemones providing anemonefish with shelter from predators in return for defence against cnidarian predators (Godwin & Fautin, ). Nepenthes bicalcarata may benefit from colony waste for nutrition (Bazile et al ., ), the prevention of nutrient export by pitcher‐dwelling Diptera (Scharmann et al ., ) and the maintenance of the slipperiness of the trap by cleaning the peristome (Thornham et al ., ).…”
Section: Divergent Evolutionmentioning
confidence: 99%
“…Furthermore, in recent years a range of studies have demonstrated various ecological adaptations related to nutrient acquisition and sometimes strongly linked to this morphological variation, such as the pitchers of Nepenthes rajah, adapted to catch the faeces of tree-shrews (Bauer et al, 2008; Ulrike Bauer et al, 2012b;Bazile et al, 2015;Clarke et al, 2009;Gaume et al, 2017;Lim et al, 2014;Merbach et al, 2002;Moran et al, 2012;Pavlovič et al, 2011;Scharmann et al, 2013;Scholz et al, 2010). These, along with variations of substrate and altitude, mark them the genus as a good putative example of an adaptive radiation (Bauer et al, 2012a;Clarke and Moran, 2016;Gaume et al, 2016;Thorogood et al, 2018).…”
Section: Introductionmentioning
confidence: 99%